Kazakhstani model of inter-ethnic relations - Amirov, N.K. (KSU publ., 2015)
The article considers the issues of successful build inter-ethnic relations in the Republic of Kazakhstan. The features of the Kazakhstan model of ensuring ethnic harmony. The analysis of inter-ethnic relations in some post-Soviet countries. Based on the conducted research the author draws a conclusion about the possibility distribution of the Kazakhstan experience of interethnic and interreligious harmony in other countries of the world.
Keywords: multinational state; multinational state; internationalism; CIS; nation; international security